Theoretical studies for the N2–N2O van der Waals complex: The potential energy surface, intermolecular vibrations, and rotational transition frequencies - Zheng, Rui (2015)
Theoretical studies of the potential energy surface (PES) and bound states are performed for the N2–N2O van der Waals (vdW) complex. A four-dimensional intermolecular PES is constructed at the level of single and double excitation coupled-cluster method with a non-iterative perturbation treatment of triple excitations [CCSD(T)] with aug-cc-pVTZ basis set supplemented with bond functions. Two equivalent T-shaped global minima are located, in which the O atom of N2O monomer is near the N2 monomer. The intermolecular fundamental vibrational states are assigned by inspecting the orientation of the nodal surface of the wavefunctions. The calculated frequency for intermolecular disrotation mode is 23.086 cm−1, which is in good agreement with the available experimental data of 22.334 cm−1. A negligible tunneling splitting with the value of 4.2 MHz is determined for the ground vibrational state and the tunneling splitting increases as the increment of the vibrational frequencies. Rotational levels and transition frequencies are calculated for both isotopomers 14N2–N2O and 15N2–N2O. The accuracy of the PES is validated by the good agreement between theoretical and experimental results for the transition frequencies and spectroscopic parameters.